2010
DOI: 10.1007/s10750-010-0533-z
|View full text |Cite
|
Sign up to set email alerts
|

Differences in growth and survivorship of zebra and quagga mussels: size matters

Abstract: The zebra mussel (Dreissena polymorpha) and its congener the quagga mussel (Dreissena rostriformis bugensis) are both invaders in freshwater, but have very different invasion histories, with zebra mussels attaining substantially faster rates of spread at virtually all spatial scales. However, in waterbodies where they co-occur, D. r. bugensis can displace D. polymorpha. To determine if the mechanisms for this displacement are associated with different survival and growth, we kept mussels in flow-through tanks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…Growth of dreissenid mussels is affected by a number of environmental factors such as food supply (Chase & Bailey, ), water temperature (MacIsaac, ; Karatayev et al ., ), depth (Garton & Johnson, ) and water chemistry (Hincks & Mackie, ). Previous studies have revealed a faster growth rate of quagga than zebra mussels, presumably resulting from lower metabolism (Baldwin et al ., ; Stoeckmann, ) and higher assimilation efficiency, especially at low food concentrations (Baldwin et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Growth of dreissenid mussels is affected by a number of environmental factors such as food supply (Chase & Bailey, ), water temperature (MacIsaac, ; Karatayev et al ., ), depth (Garton & Johnson, ) and water chemistry (Hincks & Mackie, ). Previous studies have revealed a faster growth rate of quagga than zebra mussels, presumably resulting from lower metabolism (Baldwin et al ., ; Stoeckmann, ) and higher assimilation efficiency, especially at low food concentrations (Baldwin et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, studies suggesting that dreissenid growth does not occur at low temperatures (Alimov ; Mackie ; Jantz and Neumann ; Morton a,b ) have been based on field observations during the winter, when low temperatures are coincident with low phytoplankton abundance. Our Bayesian regression analysis overcomes this limitation by synthesizing results from both lab (Karatayev et al b ) and field (this study) experiments, and highlights that both factors regulate mussel growth. Although our results suggest that the effect of food on growth are similar in magnitude to that of temperature, this estimate may be conservative because, near‐bottom growth was almost twice as fast in 2015 as in 2016, when our profundal treatments spanned the spring bloom to a greater degree (Fig.…”
Section: Discussionmentioning
confidence: 83%
“…Gradients in temperature, food, and turbulent mixing among littoral and profundal habitats are most likely responsible for observed differences in mussel growth. Many studies have observed increased growth rates at higher temperatures in quagga (MacIsaac ; Karatayev et al b ) and especially in zebra mussels (reviewed in Karatayev et al b ); similarly, the importance of food as a limiting factor for Dreissena spp. growth is well known (Dorgelo ; Sprung ; Jantz and Neumann ; Schneider et al ; Horvath and Lamberti ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The quagga mussel expends less energy on reproduction, shell development and respiration than the zebra mussel, allowing it to invest more energy in soft tissue growth (Stoeckmann, 2003;Casper and Johnson, 2010). Consequently, the quagga mussel is able to grow quicker than the zebra mussel (Baldwin et al, 2002;Karatayev et al, Table 4 Statistically significant inter-specific differences in metal concentrations found between zebra mussel (Dreissena polymorpha) and quagga mussel (Dreissena rostriformis bugensis) tissues sampled in different water types, lakes and rivers. Fig.…”
Section: Discussionmentioning
confidence: 99%